Does religiousness increase self-control and reduce criminal behavior?: a longitudinal analysis of adolescent offenders - Pirutinsky, Steven (Criminal justice and behavior, 2014)
Previous research suggests that religiousness correlates with less criminal behavior and that this relationship is partially mediated by higher self-control. Because most studies are cross-sectional, causality remains uncertain as stable between-subject factors may influence self-control, religiousness, and offending, confounding their relationships. Moreover, directionality may be reversed with higher self-control leading to both higher religiousness and less offending. The current research aimed to directly exclude these possibilities using longitudinal data from 1,354 adolescents participating in the Pathways to Desistance Study. Results indicated that short-term, within-subject increased religiousness predicted decreased future criminal behavior and that this effect was partially mediated by increased self-control. A reversed model in which past self-control predicted future religiousness was not significant. These findings suggest that religiousness may be causally related to offending, and self-control is likely one of multiple mediating processes. Additional research in this area appears warranted and may yield effective strategies for reducing criminal behavior and improving self-control.